Pre-trial Services: Responding to the Abuse of Pre-trial Detention - Zalamea León, Diego Alfredo (2024)
The aim of this article is to propose a public policy intended to ensure an appropriate use of precautionary measures, pre-trial service units. These administrative structures, on the one hand, enhance the application of alternative exits from pretrial detention and, on the other, ensure that their implementation is not synonymous with impunity and insecurity. Specifcally, this strategy addresses two central problems of traditional justice: the absence of an adequate diagnosis to choose the most suitable preventive option and the monitoring of the imposed regimen. It specifcally focuses on providing verifed information about social ties. The practical advantage is that this proposal is based on a methodology proven in the international context, in Ecuador, and recommended as a best practice by the Inter-American Commission on Human Rights. In fact, in Latin America, various experiences, whose results were  measured, reveal that the application of this strategy at different times achieved an unprecedented effectiveness in enhancing substitute measures and ensuring the appearance of individuals at trial. Even at a time when the press and the public exert pressure to increase provisional incarceration, they are a valid response, as the issued report transparently elucidates the reasons behind the adopted judicial resolution.